Pregnancy outcomes among HIV-infected women who conceived on antiretroviral therapy. - Elizabeth M Stringer; Michelle A Kendall; Shahin Lockman; Thomas B Campbell; Karin Nielsen-Saines; Fred Sawe; Susan Cu-Uvin; Xingye Wu; Judith S Currier (PLoS ONE)
As antiretroviral therapy (ART) expands in resource-limited settings, understanding the impact of ART on pregnancy outcomes is critical. We analyzed women who became pregnant on ART while enrolled in a clinical trial (HPTN 052, ACTG A5208, and ACTG A5175); the majority of women were from Africa, with a median age of 29 years. Eligible women were on ART at conception and had a documented date of a last menstrual period and a pregnancy outcome. The primary outcome was non-live birth (stillbirth; spontaneous abortion; elective termination; or ectopic pregnancy) versus live birth. Preterm birth (<37 weeks completed gestation) was a secondary outcome. We used Cox proportional hazards regression models with time-varying covariates. 359 women became pregnant, of whom 253 (70%) met inclusion criteria: 127 (50%) were on NNRTI-based ART, 118 (47%) on PI-based ART, and 8 (3%) on 3-NRTIs at conception. There were 160 (63%) live births (76 term and 84 preterm), 11 (4%) stillbirths, 51 (20%) spontaneous abortions, 28 (11%) elective terminations, and 3 (1%) ectopic pregnancies. In multivariable analysis adjusted for region, parent study, and pre-pregnancy ART class, only older age was associated with increased hazard of preterm birth [HR: 2.49 for age 25-30 years; 95% CI: 1.18-5.26; p = 0.017]. Women conceiving on ART had high rates of preterm birth and other adverse pregnancy outcomes. Despite the benefits of ART, studies designed to investigate the effects of preconception ART on pregnancy outcomes are needed.